2020
DOI: 10.1002/ps.6169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of novel insecticides on green peach aphid (Myzus persicae) feeding and transmission of Turnip mosaic virus (TuMV)

Abstract: BACKGROUND Laboratory bioassays using treated leaf disks of peach were conducted to determine the efficacy of nine insecticides against the green peach aphid (GPA), Myzus persicae (Sulzer). The effects of these insecticides on aphid feeding behaviors and rates of transmission of Turnip mosaic virus (TuMV) to potted rutabaga plants were also determined. RESULTS Median lethal concentration (LC50) values after 48 h feeding varied considerably, ranging from lows of 1.5 and 4.6 μg a.i./L for sulfoxaflor and λ‐cyhal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…15 As expected, we found that the honeydew excretion (feeding amount) of WBPH fed with rice plants treated with LC 10 and LC 50 of pymetrozine significantly decreased with increasing insecticide concentration. Similar results have been reported in Aphis fabae Scopoli, 15 Myzus persicae (Sulzer), 16,18,20 Nilaparvata lugens. 35 It is suggested that pymetrozine selectively interferes with the regulation of feeding behavior which finally results in starvation.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…15 As expected, we found that the honeydew excretion (feeding amount) of WBPH fed with rice plants treated with LC 10 and LC 50 of pymetrozine significantly decreased with increasing insecticide concentration. Similar results have been reported in Aphis fabae Scopoli, 15 Myzus persicae (Sulzer), 16,18,20 Nilaparvata lugens. 35 It is suggested that pymetrozine selectively interferes with the regulation of feeding behavior which finally results in starvation.…”
Section: Discussionsupporting
confidence: 87%
“…19 Nevertheless, in a glasshouse test, pymetrozine afforded only a modest non-significant reduction (23%) in infection of TuMV. 20 In another test, pymetrozine was not constant in reducing the spread of PVY. 21 Plant virus transmission is closely associated with specific probing behaviors of the insect vectors.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Since Shattuck (1992), many new insecticides have been released, however, some of those more effective in killing aphids, for example the neonicitinoids have been banned on most crops in Europe (Regulation (EU) No 485/2013, The European Commission, 2013). Despite recent experiments on the efficacy of nine “novel” insecticides against the green peach aphid, M. persicae , none resulted in significant reductions in rates of transmission of TuMV (Samara, Lowery, Stobbs, Vickersa, & Bittnera, 2021).…”
Section: Ecology Evolution and Controlmentioning
confidence: 99%
“…Brassica napus subsp. rapifera(Samara et al 2021). Spirotetramat, another systemic insecticide authorized on several crops in the EU (including sugar beets), inhibits lipid biosynthesis in sap-sucking insects, including mealybugs, psyllids, aphids, gall midges.…”
mentioning
confidence: 99%